2017
DOI: 10.26804/ager.2017.03.01
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulations for analyzing deformation characteristics of hydrate-bearing sediments during depressurization

Abstract: Natural gas hydrates have been treated as a potential energy resource for decades. Understanding geomechanical properties of hydrate-bearing porous media is an essential to protect the safety of individuals and devices during hydrate production. In this work, a numerical simulator named GrapeFloater is developed to study the deformation behavior of hydrate-bearing porous media during depressurization, and the numerical simulator couples multiple processes such as conductive-convective heat transfer, two-phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 37 publications
2
15
0
1
Order By: Relevance
“…On the other hand, a cubic unit of NGHs can contain approximately 180 cubic units of natural gas at standard temperature and pressure (Servio & Englezos, 2002). Therefore, NGHs have attracted much attention from academia, the industry, and the government, which has resulted in great research efforts on exploitation technology (depressurization, thermal stimulation, chemical inhibitor injection, CH 4 -CO 2 replacement, and fluidization mining method; Koh et al, 2016;Liu et al, 2017;Rutqvist et al, 2009;Tupsakhare et al, 2017;Wallmann et al, 2018;Wang et al, 2014), flow assurance (Gao, 2008;Gbaruko et al, 2007;Zerpa et al, 2011), and energy conversion (Yoneda et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a cubic unit of NGHs can contain approximately 180 cubic units of natural gas at standard temperature and pressure (Servio & Englezos, 2002). Therefore, NGHs have attracted much attention from academia, the industry, and the government, which has resulted in great research efforts on exploitation technology (depressurization, thermal stimulation, chemical inhibitor injection, CH 4 -CO 2 replacement, and fluidization mining method; Koh et al, 2016;Liu et al, 2017;Rutqvist et al, 2009;Tupsakhare et al, 2017;Wallmann et al, 2018;Wang et al, 2014), flow assurance (Gao, 2008;Gbaruko et al, 2007;Zerpa et al, 2011), and energy conversion (Yoneda et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The most common guest molecule in naturally occurring gas hydrate is methane (Waite et al, ). Gas hydrate bearing formations in nature are generally multiphase systems consisting of a formation grain matrix with water, gas, and hydrate occupying the pore space (Liu et al, ; Sun & Goldberg, ). Scientific interest in gas hydrate has increased tremendously in recent decades due to the decline of conventional fossil fuel resources.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that c ic * values generally stay close to the horizontal red line c ic * = 1 (Figure 7(c)), and c if * values go through an evolutionary process from below to above the red curve c if (Figure 7(d)). These discrepancies between numerical simulated c ic,f * data and corresponding theoretical models (i.e., Equations (8) and (12)) are mainly due to differences in hydrate pore habits since grain-coating and pore-filling hydrate growths can hardly follow the uniform and self-similar way ( Figure 5 Figure 8. It is obvious that hydrate saturation and morphology effects on c i and c i * values are similar with those on c h and c h * values.…”
Section: Geofluidsmentioning
confidence: 97%
“…Currently, the exploitation of this potential energy resource is still not economically feasible and requires innovative production methods and techniques [4,5]. New methods and techniques should be well evaluated by numerical simulators prior to field applications, and results of these numerical evaluations largely depend on proper characterizations of coupled processes and appropriate quantifications of physical properties of hydrate-bearing sediments [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%